Antifungal Activity of Endophytic Bacteria Associated with Sweet Sorghum (Sorghum bicolor) - Siti Meliah; Tri Ratna Sulistiyani; Puspita Lisdiyanti; Atit Kanti; I Made Sudiana; Masaru Kobayashi (Institute for Research and Community Services (LPPM) ITB, 2021)
The contribution of endophytic bacteria to the wellbeing of plants as biocontrol agents may be due to endophytic bacteria growing in the same niche as phytopathogens. This work was conducted to study the antagonistic activity of endophytic bacteria recovered from sweet sorghum against Sclerotium rolfsii, Fusarium solani, Fusarium oxysporum, Colletotrichum gloeosporioides in vitro and evaluate the mechanisms of these fungal inhibitions. We selected 78 endophytic bacteria from the stem and root of sweet sorghum plants. They were tested for antagonist activity by direct confrontation method. Antifungal compound production and lytic enzyme activity were examined to determine their mechanisms in inhibiting fungal pathogens. Antifungal compound production was checked by detecting the presence of NRPS and PKS genes. Lytic enzyme activity of the bacteria was evaluated by their ability to produce cellulase, chitinase, and protease. Selected bacteria were identified using molecular analysis based on the 16S rRNA gene. 14 out of the 78 tested isolates showed antagonistic activity and two were able to inhibit all four tested fungal strains. Four bacteria, designated as ACIL1, ACNM4, ACNM6, and ATNM4, produced natural products via NRPS pathway, but only one bacterial extract, designated as ACNM4, showed fungal inhibition. Ten isolates were able to produce hydrolytic enzymes. Endophytic bacteria identified as Burkholderia were revealed to have potential as a biocontrol agent.